STRUCTURAL STYLE OF WABI FIELD, OFFSHORE NIGER DELTA NIGERIA, USING SEISMIC AND WELL-LOG DATA - Amakiri, S., Uko, E. D; Tamunobereton-ari (Geological Behavior)
This study is focused on the interpretation of structural style in Wabi field in the Niger Delta Nigeria using seismic and well log data. From the results, faults and horizons correlated on Wabi wells tied perfectly to reflections on the seismic. The faulting pattern shows that the structural geometry over the Wabi field consist of an elongated N-W to S-E trending, collapsed crest, roll-over structure with two crests separated by a central saddle. Based on their lateral extent and throws Faults in Wabi Field is classified into boundary faults that confined the Wabi structure, synthetic and antithetic faults are within the crestal roll-over structure. The interplay of these faults, combined with the structural dip, provides the closure for the hydrocarbon accumulation within the field. Hydrocarbons in the field are encountered between 9,560 and 12,750ftss, and are contained within 3 stacked B, O, and R1 reservoirs in crestally collapsed rollover anticline. The reservoirs are predominantly shore face and are correlatable throughout the Field. Well correlation and sand analysis showed that sand R1 was the thickest sand unit by 320ft. Sand B is the thinnest sand unit in Wabi Field, it is 50ft. Results from this study provides interpretation and modelling of structural and stratigraphic interplays that would help in understanding of the feature and factors that control them reservoirs thereby creating room for predictive models that can be applied in other reservoirs at greater depth prospects. This helps to make informed decisions for optimum exploration and development of hydrocarbons in the field of study.